miR-3587 Inhibitor Attenuates Ferroptosis Following Renal Ischemia-Reperfusion Through HO-1 - Tao, Wenqiang; Liu, Fen; Zhang, Jianguo; Fu, Shangmiao; Zhan, Hui; Qian, Kejian (Frontiers in Molecular Biosciences, 2022)
Renal ischemia-reperfusion (IR) is frequently observed in patients who are critically ill, yet there are no reliable or effective approaches for the treatment of this condition. Ferroptosis, a form of programmed cell death, is regulated by key genes such as glutathione peroxidase 4 (GPX4) and heme oxygenase-1 (HMOX1) and participates in the injury of renal tubular epithelial cells during IR. This study aimed to investigate the miRNA-mRNA regulatory networks involved in ferroptosis following renal IR. Using bioinformatics analysis, HMOX1 was found to be significantly upregulated during the early stages of renal IR injury, and microRNA-3587 (miR-3587) was identified as a putative regulator of HMOX1. When a miR-3587 inhibitor was applied in a hypoxia-reoxygenation (HR) model system using renal tubular epithelial cells, HO-1 protein (encoded by HMOX1) expression was significantly increased relative to that observed in the HR group, with concomitant increases in GPX4 protein levels, enhanced cell viability, a reduction in malondialdehyde content, decreased Fe2+ level, and the restoration of normal mitochondrial membrane potential. Transmission electron microscopy showed a reduced or absent mitochondrial crest and a damaged mitochondrial outer membrane. Targeting of HMOX1 by miR-3587 was confirmed by luciferase reporter gene assay. In conclusion, these preliminary results indicate that inhibition of miR-3587 promotes HO-1 upregulation, thereby protecting renal tissues from IR-induced ferroptosis.